1993
DOI: 10.1038/bjc.1993.407
|View full text |Cite
|
Sign up to set email alerts
|

Functional and histological bladder damage in mice after photodynamic therapy: the influence of sensitiser dose and time of administration

Abstract: Summary The bladders of anaesthetised mice were illuminated with red laser light (630 nm) at intervals of I day to 4 weeks after i.p. administration of Photofrin. Light was delivered intravesically by inserting a fibre optic, with a diffusing bulb tip, into the centre of fluid filled bladders. A single light dose of 11.3 J cm-2 applied 1 day after 10 mg kg-' Photofrin caused a severe acute response, with increased urination frequency (five to seven times control) and haematuria. Recovery was good, however, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Because the UFI derived from daily urinary spots for rats of moderate size (160–200 g) over the 2 weeks before PDT was so consistent, this method was adopted for the present study. Despite the differences in the animal model, animal size and experimental design from that of Stewart et al , the increased voiding irritation seen in the first 2 weeks after PDT in the present study was comparable to that reported in theirs, which used Photofrin II (10 mg/kg) in the H3C mouse bladder [29,30]. They concluded that the UFI and the time interval to return to normal voiding was linearly related to the dose of light.…”
Section: Discussionsupporting
confidence: 82%
“…Because the UFI derived from daily urinary spots for rats of moderate size (160–200 g) over the 2 weeks before PDT was so consistent, this method was adopted for the present study. Despite the differences in the animal model, animal size and experimental design from that of Stewart et al , the increased voiding irritation seen in the first 2 weeks after PDT in the present study was comparable to that reported in theirs, which used Photofrin II (10 mg/kg) in the H3C mouse bladder [29,30]. They concluded that the UFI and the time interval to return to normal voiding was linearly related to the dose of light.…”
Section: Discussionsupporting
confidence: 82%
“…However, it is well-recognized that PDT is not yet optimized in this respect. For example, several reports have documented PDT-related injuries on normal tissues in clinical Takita et al, 1994) and experimental (Pelton et al, 1992;Ris et al, 1993aRis et al, , 1993bStewart et al, 1993;Ji et al, 1994;Tochner et al, 1994;Veenhuizen et al, 1994) settings. Thus, there have been many efforts to improve selective action; for example, by developing new photosensitizers, modulating drug-light conditions, and improving light dosimetry (Ash and Brown 1993;Levy 1994).…”
mentioning
confidence: 99%
“…Photofrin (Quadra Logic Technologies, Vancouver, Canada) was given at a standard, high dose of 10 m g k g 1 day before whole bladder illumination with light doses of 2.7-10.8 J/cm2 as previously described (1 3,14). This drug/dose schedule was chosen based on previous experiments which demonstrated that 5-10 mg/ kg Photofrin given 1-7 days before bladder illumination caused moderately severe acute damage with recovery within 12 weeks after light doses 57.5 J/cm2 (13,14). The drug was supplied as a freezedried preparation that was dissolved in 5% dextrose to a concentration of 2.0 mg/mL as previously described ( 1 3).…”
Section: Methodsmentioning
confidence: 99%
“…The photosensitizer BCA was given in a dose of 10-30 m g k g I h before 5.4-32.5 J/cm2 whole bladder illumination (this time interval was selected based on previously published results that demonstrated good fluorescence intensity in tissue at 15-60 min after BCA injection (12)). The bladders of mice were illuminated as previously described (13). Prior to illumination the mice were anesthetized (60 mg/kg sodium pentobarbitone, intraperitoneally) their bladders were emptied with a catheter (V190 Venflon 22W0.8 mm) and filled with 0 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation